PENGARUH PENAMBAHAN SODIUM TRIPOLIPHOSPHAT (STPP) TERHADAP MUTU TEPUNG SURIMI - Amahorseja, Anggeline Lioni (Hibualamo : Seri Ilmu-Ilmu Alam dan Kesehatan, 2017)
The purpose of this research was to know the effect of addition of sodium tripoliphosphat (STPP) for the quality of surimi powder. This research is expected to give information to the public about surimi powder and the effect of adding sodium tripoliphosphat (STPP) on quality surimi powder. The results of variety analysis showed that the addition of sodium tripoliphosphat (STPP) concentration is very real effect on the value of protein content, water absorption and kamba density of surimi powder, while not significantly affect the value of water content. The average water content values ranged of surimi powder 12,32% - 18.49%. The average value of protein content ranged between 70.58% - 77.70%, while for the value of water absorption and kamba density ranged between 1.6% - 1.87% and 0.53 g/ml - 0.67 g/ml.